2016
DOI: 10.1177/0003319715621996
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Endothelial Cell–Specific Molecule 1 Level in Stress Hyperglycemia Patients With Acute ST-Segment Elevation Myocardial Infarction

Abstract: Endothelial cell-specific molecule 1 ([ESM-1], endocan) is a new biomarker of endothelial dysfunction, which may be involved in the pathogenesis of atherosclerosis and stress hyperglycemia in patients with acute ST-segment elevation myocardial infarction (STEMI). Therefore, we investigated serum ESM-1 levels in patients with stress hyperglycemia having STEMI; 105 patients with STEMI and 33 individuals as a control group were included in the study. The patients were followed up for 3 months and major adverse ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…ESM‐1 was recognized as an important endothelial marker 11 . Our previous research indicated that ESM‐1 levels > 1.01 ng/mL were an independent indicator of major adverse cardiac events in patients with stress hyperglycemia having STEMI 12 . The correlation between EMS‐1 and high‐sensitivity C‐reactive protein levels and the neutrophil to lymphocyte ratio was also revealed in our investigation 13 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…ESM‐1 was recognized as an important endothelial marker 11 . Our previous research indicated that ESM‐1 levels > 1.01 ng/mL were an independent indicator of major adverse cardiac events in patients with stress hyperglycemia having STEMI 12 . The correlation between EMS‐1 and high‐sensitivity C‐reactive protein levels and the neutrophil to lymphocyte ratio was also revealed in our investigation 13 .…”
Section: Discussionsupporting
confidence: 76%
“…In recent years, endothelial cell‐specific molecule 1 (ESM‐1) was recognized as an important endothelial marker, 11 which may be involved in the pathogenesis of atherosclerosis and lead to endothelial dysfunction 12 . The serum ESM‐1 level was suggested to be a novel biomarker for the diagnosis, evaluation, 12,13 or even staging 14 of acute STEMI. However, Aparci et al 15 .…”
mentioning
confidence: 99%
“…29 Elevated ESM-1 level may be associated with CVD. [30][31][32][33] Balta et al measured serum ESM-1 levels in 18 newly diagnosed patients with untreated essential hypertension (HT) and 23 control participants; serum ESM-1 levels were significantly higher in the HT group. 7 They also applied receiver-operating characteristic curves to predict the activity of HT and determine the cutoff value.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell-specific molecule 1 (ESM-1) is a new biomarker of endothelial dysfunction, which is involved in the pathogenesis of atherosclerosis and stress induced hyperglycemia in patients. Admission glucose levels are associated with ESM-1 levels, and ESM-1 is an independent predictor of major adverse cardiac events [33]. Abnormal glycemic status is associated with carotid atherosclerosis, from early signs as demonstrated by the IMT presence of carotid plaques, to advance atherosclerosis [34].…”
Section: Discussionmentioning
confidence: 99%